New records of robber flies (Diptera: Asilidae) from Belarus - Sakhvon, Vital V. (Experimental Biology and Biotechnology, 2017)
New records of robber flies (Diptera: Asilidae) from Belarus are presented, with new distribution records for 18 species: Leptogaster cylindrica (De Geer, 1776), L. guttiventris Zetterstedt, 1842, Antipalus varipes (Meigen, 1820), Asilus  crabroniformis Linnaeus, 1758, Dysmachus trigonus (Meigen, 1804), Echthistus rufinervis (Meigen, 1820), Erax barbatus Scopoli, 1763, Neomochtherus pallipes (Meigen, 1820), Pamponerus germanicus (Linnaeus, 1758), Tolmerus atricapillus (Fallen, 1814), T. cingulatus (Fabricius, 1781), Choerades marginata (Linnaeus, 1758), Dioctria atricapilla Meigen, 1804, D. hyalipennis (Fabricius, 1794), D. oelandica (Linnaeus, 1758), D. rufipes (De Geer, 1776), Cyrtopogon lateralis (Fallén, 1814) and Lasiopogon cinctus (Fabricius, 1781). One subfamily: Stenopogoninae and two species: Dysmachus trigonus (Meigen, 1804) and Cyrtopogon lateralis (Fallén, 1814) are recorded from Belarus for the first time. So, at present moment the fauna of robber flies of Belarus includes 38 species.
Keywords: robber flies; fauna; Belarus; Asilidae; new records